Проблема вибору організаційної структури управління малим підприємством - Добролежа, К.М.; Михальчук, Л.В. (Культура народов Причерноморья, 2014)
Однією з найважливіших проблем розвитку малих підприємств в Україні є недосконалість
управлінської структури. Охарактеризовані у статті організаційні структури управління
підприємством, більше відповідають малим підприємствам, а також наводяться їх переваги та
недоліки. Приділяється увага недолікам існуючої наразі на малих підприємствах управлінської концепції
«підприємницького чуття», яка знецінює всі функції управління підприємством. Переваги систем
управління на малих підприємствах мають підкріплюватися формальними зв’язками між структурними
відділами, а вдосконалення структури управління дозволить розвивати бізнес та вносити до нього
інновації. Одной из важнейших проблем развития малых предприятий на Украине является
несовершенство управленческой структуры. Охарактеризованные в статье организационные
структуры управления предприятием, больше соответствуют малым предприятиям, а также
приводятся их преимущества и недостатки. Уделено внимание недостаткам существующей на малых
предприятиях управленческой концепции «предпринимательского чутья», которая обесценивает все
функции управления предприятием. Преимущества системы управления на малых предприятиях
должны подкрепляться формальными связями между структурными подразделениями, а
совершенствование структуры управления позволит развивать бизнес и вносить в него инновации. Small business is a key part of the market economy, which greatly affects the socio-economic
development of the country. The article explores the main features of small business, particularly the attention is
paid to the phases of development. One of the major problems of development of the small enterprises in Ukraine
is imperfection of governance structure. From the traditional standpoint here concepts of organizational
enterprise management system are considered, the characteristics of two most common types of organizational
structures - linear and linear-functional are showed. Authors examined the organizational structures of
enterprise management which is most correspond for small businesses, also their advantages and disadvantages
were given. Much attention is paid to the disadvantages of small enterprises management concept of
"entrepreneurial flair" which devalues all the functions of management. The outstanding characteristics of small
business management systems that contribute to its functioning are identified. Authors determined that the
benefits of management systems for small businesses are supported by formal connections between structural
divisions, and improving the management structure will enable the business to develop and introduce
innovations to it. Improving management is one of the essential ways to modernize small business to market
requirements along with the traditional production of competitive goods.